KNOWLEDGE ORGANIZATION SYSTEMS IN THE BRAZILIAN AMAZONIAN CONTEXT:: a case study in museums and libraries at UFPA - Fonseca, Luciana Di Paula Andrade da; Carvalho, Raul de Azevedo; Redigolo, Franciele Marques; Assunção, Suelene Santana; Moreira, Rosana Patrícia dos Santos (Informação em Pauta, 2025)
Interoperability between Knowledge Organization Systems presupposes the use of standards and mappings that enable data communication between different institutions. In this context, the article aims to: Investigate the Knowledge Organization Systems used and the challenges of mapping vocabularies in search of semantic interoperability between different information units at the Federal University of Pará, in accordance with the ISO 25964-1/25964-2 standard. The methodology consists of a case study, using semi-structured interviews and questionnaires, applied to seven information units at the Federal University of Pará. As a result, it was observed that the information units have their own controlled vocabularies, making it possible not to carry out mappings between vocabularies, which is an obstacle to achieving semantic interoperability between the different Knowledge Organization Systems. It was concluded that the practice of mapping between vocabularies, following the ISO 259641/25964-2 standard, may be relevant for thinking about building their own controlled vocabularies, both in museums and libraries, as their users can benefit from communication between these different institutions through semantic interoperability.